34 Inspiring the future generation of oncologists: a UK-wide study of medical students' views towards oncology. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Rallis, Kathrine; Wozniak, Anna Maria; Hui, Sara; Nicolaides, Marios; Shah, Neha; Subba, Beena; Papalois, Apostolos; Sideris, Michail
Abstract : Background: One in 2 people born in the UK after 1960 are expected to require oncology input in their lifetime. However, only 36% of UK medical schools provide dedicated oncology placements and teaching indicating a discordance between public health impact and training. We designed a UK-wide survey to capture medical students' views on current oncology teaching and the potential role of a national undergraduate oncology symposium as an educational, networking and motivational tool. Methods: We undertook a national cross-sectional survey of UK medical students' views in oncology and satisfaction with teaching using pre-designed questionnaires. We also distributed a dedicated survey (pre and post-conference) to compare medical students' motivation towards a career in oncology after attending the national symposium. This study was prospectively approved by QMUL Ethics Committee (Reference number QMREC2348). Statistical analysis included univariate inferential tests on SPSS and GraphPad software. Results: The national survey was completed by 166 students representing 22 UK medical schools. Students reported limited interest, knowledge and exposure to oncology, lack of confidence in skills, and teaching dissatisfaction. Oncology was perceived as a challenging specialty (mean Likert score: 4.5/5±0.7), yet most students estimate receiving only 1–2 weeks of dedicated oncology teaching. The national symposium generated a statically significant increase in students' interest (p=0.0012), knowledge, and confidence in skills surrounding oncology (p<0.0001), improving students' perceived ability to cope with the emotional challenges in this field (p=0.0278). Conclusion: Students' unimpressive views towards oncology alongside their teaching dissatisfaction underpin the need to reform current undergraduate oncology curricula. Increasing medical student oncology exposure by proposing outcome-based guidelines and adopting a standardised undergraduate oncology curriculum should be the foremost priority in inspiring future oncologists to ensure excellent cancer patient care.